Insight into global research on health literacy and heart diseases: A bibliometric analysis - Huy, Le Duc; Truong, Nguyen L. T.; Hoang, Nhi Y.; Nguyen, Nhi Thi Hong; Nguyen, Thao T. P.; Dang, Loan T.; Hsu, Yi-Hsin Elsa; Huang, Chung-Chien; Chang, Yao-Mao; Shih, Chung-Liang; Carbone, Elena T.; Yang, Shwu-Huey; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Health literacy (HL) has shown its important role on reducing the burden of heart diseases. However, no study has provided a comprehensive worldwide view of the data regarding HL and heart diseases. The study aimed to provide insight into: (1) the intellectual structure, (2) research trends, and (3) research gaps on HL and heart diseases; and (4) to explore HL scales commonly utilized in heart studies. Materials and methods Studies related to HL and heart diseases were retrieved from Web of Science, Scopus, and PubMed. All publications published between 2000 and 2021 were included after conducting keyword searches on “heart diseases” in general or on specific types of heart diseases (e.g., “heart failure”) and “health literacy”. Bibliometric analyses were carried out using the Bibliometrix R package and VOSviewer 1.6.14. Findings A total of 388 original research articles and reviews on HL and heart diseases were included in our study. The studies were primarily conducted in the United States and developed countries. A total of 337 studies (86.9%) focused on heart failure (200 studies, 51.5%) and ischemic heart diseases (137 studies, 35.3%). Sixty-two studies (16.0%) focused on other heart diseases (e.g., valvular diseases and rheumatic heart diseases). The number of interventional studies was limited (52 studies, 13.4%) and fluctuated from 2000 to 2021. The most common questionnaires measuring health literacy among patients with heart diseases were the Test of Functional Health Literacy in Adults (TOFHLA), Short Test of Functional Health Literacy in Adults (STOFHLA), and Brief Health Literacy Screen (BHLS). Use of the eHealth Literacy Scale (eHEALS) has become the latest trend among patients with heart diseases. Conclusion Health literacy and heart diseases were most often studied in the United States and developed countries. Several HL tools were used; eHEALS has been lately used in this field. These findings suggest the need to conduct more empirical studies on HL and heart diseases in different settings (e.g., developing or poor countries) and with different types of heart diseases (e.g., valvular and rheumatic disorders). Additionally, it is necessary to develop heart disease-specified HL scales for research and practice.